Speed Improves With Eccentric Hamstring Training in Athletes of Different Maturity Status - Hammami, R.; Gene-Morales, J.; Nebigh, A.; Rebai, H.; Colado, J. C. (Pediatric Exercise Science, 2022)
Purpose: To investigate the effects of an eccentric hamstring strength training program (EHT) on sprint performance (10-, 20-, and 30-m sprint times) and change of direction speed (4 × 5-m shuttle run and T-Half test) in male European handball athletes at 2 maturity statuses (prepeak and postpeak height velocity [PHV]). Methods: Forty-five participants (12.68 [1.58] y) were divided into pre-PHV and post-PHV and randomly allocated to a control or intervention group, which performed a guided 2 day per week 6-week EHT of 5 exercises. A mixed-model (within- and between-factor) analysis of variance was conducted. Results: A significant effect (P < .05) of the interaction time × maturity × training was observed in the T-Half, 10, and 30 m tests. Both intervention groups significantly improved in all the tests, except in the 20 m sprint and the post-PHV in the 10 m sprint. Improvements ranged between 0.93% and 5.74% (effect size: 0.07-0.79). Both control groups yielded no improvements in almost all the tests. The improvements of both groups undergoing the intervention (pre-PHV and post-PHV) were not significantly different (only a tendency in the 10 m sprint). Conclusion: An EHT program combined with European-handball training improve change of direction and sprint performance in pre-PHV and post-PHV male players. Professionals training European handball and similar team-sport athletes should consider including EHT regardless of athlete`s maturity